Impact of Agency Costs, Board Environmental Committee, Board Gender Diversity, Environmental Performance and Institutional Ownership on Firm Performance - Yandi Suprapto; Nicholas Sunaidi; Hesniati Hesniati (Universitas Pendidikan Indonesia, 2025)
The research objective is to evaluate the effect of environmental corporate governance on firm performance measured by return on assets. The independent variables consist of environmental performance, board gender diversity, institutional ownership, agency costs, and board environmental committee. This study involved 260 observations of 52 Indonesian companies from the energy sector in the 2018-2022 period. The results of this study indicate that there is a significant relationship between environmental performance and board environmental committee on firm performance of Indonesian companies in the energy sector. Meanwhile, board gender diversity and institutional ownership show no significant relationship to firm performance of Indonesian companies in the energy sector. Lastly, low agency costs are proven to show a significant relationship towards firm performance. In this research, agency cost measured by total asset turnover significantly improves the firm’s return on assets. The results of this study provide additional knowledge about the relationship between environmental corporate governance towards firm performance.